Regioselective Nitration of Aromatic Hydrocarbons with Bentonite Supported Metallic Nitrates in the Presence of Solid Acids Catalysts - Zhang, H.; Peng, X.; Yuan, L. (Asian Journal of Chemistry, 2012)
Toluene and chlorobenzene are mononitrated of good regioselectivities using metallic nitrates as nitrating reagents in the presence of solid acid catalysts. Para selectivities are much improved, up to para-to-ortho ratios of 1.2 for toluene and 5.6 for chlorobenzene respectively.